2021
DOI: 10.1111/jcmm.17055
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐411‐3p inhibits bleomycin‐induced skin fibrosis by regulating transforming growth factor‐β/Smad ubiquitin regulatory factor‐2 signalling

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…During EMT and fibrosis, the downstream Smad (a transcriptional regulator of TGF-β) signaling pathway is upregulated . Quantification of Smad proteins following tFNA treatment indicated that Smad2/3 levels decreased by ∼50% relative to levels in control cells (Figure a,g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During EMT and fibrosis, the downstream Smad (a transcriptional regulator of TGF-β) signaling pathway is upregulated . Quantification of Smad proteins following tFNA treatment indicated that Smad2/3 levels decreased by ∼50% relative to levels in control cells (Figure a,g).…”
Section: Resultsmentioning
confidence: 99%
“…During EMT and fibrosis, the downstream Smad (a transcriptional regulator of TGF-β) signaling pathway is upregulated. 42 Quantification of Smad proteins following tFNA treatment indicated that Smad2/3 levels decreased by ∼50% relative to levels in control cells (Figure 2a,g). These results demonstrated tFNAs as potent nanoscale therapeutic agents for suppressing EMT and eliminating ECM protein deposition, suggesting them as a potential nanoscale therapy for treating skin fibrotic diseases.…”
Section: ■ Materials and Methodsmentioning
confidence: 95%
“…This outcome differed from the presentation of rosacea-like lesions induced by short-term LL-37 administration [ 32 ] but was similar to what we have seen in previous studies employing intradermal injections of LL-37 every 24 h for 20 days [ 33 ]. In addition, in studies on bleomycin-induced skin fibrosis, collagen deposition was found to be accompanied by the thickening of both the dermis and epidermis, as well as the upregulation of α-smooth muscle actin and wave protein expression levels [ 34 , 35 ]. In our constructed mouse rosacea model, in addition to the inflammatory manifestations, the above manifestations of skin fibrosis also appeared, which indicates that the rosacea progressed from inflammation to skin fibrosis and further indicates that it is feasible to construct a model of advanced rosacea fibrosis by prolonging the duration and frequency of LL-37 intradermal injections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inflammatory role of some miRNAs, other candidates have been involved in fibrosis or proliferation. For instance, miR-411-3p has been shown to alleviate pulmonary and skin fibrosis through modulation of TGF-β/Smad ubiquitin regulatory factor 2 (Smurf 2) signaling, whereas miR-491-5p inhibits the non-small cell lung cancer (NSCLC) cell proliferation and migration by targeting forkhead box P4 (FOXP4), a transcription factor involved in the regulation of various cancers [42][43][44]. However, the implication of the remaining seven novel miRNAs (miR-7061-5p, 381-3p, miR-7224-3p, 3097-5p, miR-6540-5p, 33-3p, and 1943-5p) in lung biology still unknown.…”
Section: Discussionmentioning
confidence: 99%